SEMANTICS OF ADJECTIVES-ANTONYMS IN ENGLISH AND UZBEK: A COMPARATIVE ANALYSIS OF GOOD/NICE AND BAD/YOMON (International journal of artificial intelligence, 2026)
This article presents a comparative semantic analysis of antonymous adjectives in English and Uzbek, focusing on the conceptual pairs good/nice and bad/yomon. The study explores the polysemy, connotative nuances, and pragmatic functions of these lexical units in both languages. While English distinguishes between good (moral/functional quality) and nice (pleasantness/social agreeableness), Uzbek utilizes yaxshi as a broader superordinate term covering both meanings, with yomon serving as its direct opposite. The research employs contrastive analysis, componential analysis, and contextual interpretation methods to reveal structural and functional divergences. Findings indicate that cultural values significantly influence the semantic fields of evaluation, with English exhibiting higher lexical differentiation in social contexts, whereas Uzbek relies more on contextual modulation and intensifiers. The study contributes to cross-cultural linguistics and translation studies by highlighting the challenges of equivalence in evaluative vocabulary.